Achieving a Soft Landing : The Role of Fiscal Policy - Leigh, Daniel (Washington, D.C. : International Monetary Fund, 2008)
This paper utilizes an open-economy New Keynesian overlapping generations model to assess the extent to which fiscal policy, along side an inflation-forecast-based monetary policy, could enhance macroeconomic stability in Colombia. The model simulations indicate that, in addition to stabilizing output and inflation, a stronger response of the fiscal balance to excess tax revenue would reduce the burden on the central bank of adjusting interest rates, lessen the associated degree of exchange rate volatility, and contribute to a more stable external current account balance. The analysis also assesses how the success of fiscal policy in enhancing macroeconomic stability depends on the type of shock, the response of monetary policy, and the length of fiscal policy implementation lags.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet